An Approach to Mathematical Modeling and Estimation of Probe-Drogue Docking Success Probability for UAV Autonomous Aerial Refueling - Xufeng Wang; Jianmin Li; Xingwei Kong; Xinmin Dong; Bo Zhang (International Journal of Aerospace Engineering)
One of the keys to the success of aerial refueling for probe-drogue aerial refueling system (PDARS) is the successful docking between the probe and drogue. The study of probe-drogue docking success probability offers an important support to achieving successful docking. During the docking phase of PDARS, based on prior information and reasonable assumptions for the movements of the drogue under atmospheric disturbance, the probe-drogue docking success probability is converted to the probability of the drogue center located in a specific area. A model of the probe-drogue docking success probability is established with and without actuation error, respectively. The curves of the probe-drogue docking success probability with the standard deviation of the drogue central position, the maximum distance from the drogue center position to the equilibrium position, the actuation error, and the standard deviation of the actuation error are obtained through simulations. The study has referential value for the docking maneuver decision of aerial refueling for PDARS.